Fusariosis control in black pepper plants with bacterial endophytes: survival and morphophysiological responses - Benchimol, Ruth Linda; Chu, Elizabeth Ying; Muto, Roberto Yuiti; Filho, Moacyr Bernardino Dias (Pesquisa Agropecuaria Brasileira, 2000)
Eight endophytic bacteria from black pepper seedlings were tested under greenhouse conditions aiming to control Fusarium solani f. sp. piperis and to evaluate some morphophysiological responses in plants treated with the biocontrol agents. Four-month old plants had their roots treated with the bacterial suspensions (109 cfu mL-1) for 10 minutes and were planted in pots containing soil artificially infested with the pathogen (0.25%). The experimental design was completely randomized, with three replications to evaluate photosynthetic behavior, and biomass production and allocation, and five replications to evaluate plant mortality. Evaluations were made 120 days after the establishment of the experiment. The isolate B0 (Methylobacterium radiotolerans) significantly reduced seedling mortality by fusariosis. No significant effect in seedling mortality reduction could be detected for the other bacterial isolates. In the absence of the pathogen, M. radiotolerans acted as a plant growth promoter. The application of the bacterial endophytes had no effect on the instantaneous photosynthetic rate, with the exception of B6, that had a negative effect. Plants treated with M. radiotolerans allocated carbon preferentially to the above ground tissues.